Surfactant Assisted In Situ Synthesis of Nanofibrillated Cellulose/Polymethylsilsesquioxane Aerogel for Tuning Its Thermal Performance. Issue 2 (25th October 2022) - Gupta, Pragya; Sathwane, Manoj; Chhajed, Monika; Verma, Chhavi; Grohens, Yves; Seantier, Bastien; Agrawal, Ashish K.; Maji, Pradip K.
Abstract: Nanofibrillated cellulose (NFC) and polymethylsilsesquioxane (PMSQ) based aerogel are prepared by the sol‐gel method. The objective of this work is to study the impact of surfactant and base catalyst on the thermal and mechanical performance of the corresponding aerogel. The rheological premonitory assists in predicting the bulk properties of the aerogel. The chemical structure of the aerogel is studied by Fourier‐transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and solid‐state nuclear magnetic resonance (NMR). X‐ray microtomographic (XMT) analysis confirms the homogeneous and monolithic structure of the aerogel. The lowest thermal conductivity is achieved as 23.21 mW m −1 K −1 with V‐0 and HBF rating through UL‐94 test. Thermal performance of aerogels is cross‐verified through modeling and simulation in COMSOL multiphysics platform. The mechanical properties of aerogel are evaluated by monolithic compression test in axial and radial compression test up to 90% strain, cyclic compression loading–unloading, and reloading test, flexural test, and dynamic mechanical analysis. The time‐temperature analysis has shown around 5 °C temperature difference in the middle of the room after using the aerogel panel at the exposed surface, which assists in the practical application of the synthesized aerogel panel. Abstract : In present work, thermal conductivity is dependent upon solid and gaseous conductivity. Green color fibers and spherical particles symbolizes for nanofibrillated cellulose (NFC) and polymethylsilsesquioxane (PMSQ). The differentiation in the amount of PMSQ directly reflects on the thermal conductivity of aerogel. The thermal conductivity is found between 23.21 and 31.32 mW m −1 K −1 . The present work is compared with other published reports.